Implication of service marketing in POS (point of sales) acquiring business of BRAC Bank Limited - Shad, Md. Nowfel (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.